Pengaruh Akun Media Sosial Instagram @pemudahijrah Terhadap Perilaku Sosial Pada Remaja: Studi Pada Siswa-Siswi MAN Model Sorong - Ardianto, Ardianto; Yudiawan, Agus (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
This study aims to find the effect of the @pemudahijrah Social Media Account on the Social Behavior of Adolescents at MAN Model Sorong City. This type of research is quantitative, using a descriptive approach. The population in this study were all students of MAN Model Sorong who followed the @pemudahijrah account; as many as 200 people were divided into three grade levels, while the sample taken was 133 people. The research instrument used a Likert scale questionnaire. The data that has been collected is then processed using the SPSS 24.0 application for windows. Research shows that the f-count is 26,748. So that it can be concluded that f-count (26,748) > f-table (2,74), it can be stated that H1 is accepted and H0 is rejected or it can be stated that there is an influence of the Instagram social media account @pemudahijrah (X) on the social behavior of adolescents in MAN Model Sorong (Y). The value of the coefficient of determination indicates that 17% of the variables of adolescent social behavior in MAN Model Sorong is the contribution of the Instagram social media account variable @pemudahijrah and other reasons explain the additional 83%.